Evaluation of Sustainable Agricultural Practices Using Organic Fertilizers for Soil Recovery in Salache: A Neutrosophic Superhypersoft Set Approach - 10.5281/zenodo.14418601; Julio Cesar Alegre Orihuela (Neutrosophic Sets and Systems)
Modern agriculture faces critical challenges due to soil degradation and the urgent need for sustainable practices to preserve the environment. This study analyzed the impact of organic fertilizers, including vermicompost, compost, manure, and control, on the development of Lupinus mutabilis and Pisum sativum. Different groups were evaluated based on chemical and physical soil properties, plant attributes, and crop cycles using Neutrosophic SuperHyperSoft Sets. The results demonstrated that vermicompost is the most effective option for optimizing soil properties and improving crop yields. In conclusion, the use of vermicompost and other organic sources is proposed as an effective strategy to enhance soil fertility and crop productivity, particularly in degraded lands, while fostering the adoption of more sustainable agricultural practices.